PELAKSANAAN PENGAWASAN BPD DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI KECAMATAN SUMEDANG UTARA KABUPATEN SUMEDANG - Andhika Tri Adhilla Nugraha (JRPA - Journal of Regional Public Administration, 2026)
This study aims to determine how the Village Supervisory Board (BPD) supervises village administration in North Sumedang Subdistrict, identify factors that hinder its implementation, and efforts made to overcome these obstacles. The implementation of the BPD's supervisory functions is crucial given the dynamic changes in regulations, increasing demands for public accountability, and the complexity of village governance. Therefore, a systematic and participatory supervisory mechanism is needed to ensure that village governance aligns with the principles of good governance. This study employs a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The research subjects consist of BPD members, village heads, village officials, and community leaders. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to describe the reality of oversight implementation holistically. The research results indicate that BPD oversight implementation encompasses three main dimensions: setting standards, measuring performance, and correcting deviations. However, its implementation has not been optimal due to various obstacles, such as the lack of supervision SOPs, low understanding of program success indicators, weak coordination between BPD and village heads, and minimal documentation of supervision results. Efforts to overcome these obstacles include technical training on supervision, increasing the frequency of deliberations, and strengthening the institutional capacity of the BPD through support from the sub-district and village governments. This study is expected to serve as a reference for local governments, village institutions, and other stakeholders in designing strategies to strengthen the supervisory functions of the BPD in an effective and sustainable manner, thereby fostering transparent, participatory, and accountable village governance.